2018
DOI: 10.4081/monaldi.2018.944
|View full text |Cite
|
Sign up to set email alerts
|

The value of exfoliative cell cytology in the diagnosis of exudative pleural effusions

Abstract: The sensitivity and specificity of exfoliative cell cytology for the diagnosis of exudative pleural effusions varies widely according to the etiologic causes. The aim of this study is to assess the diagnostic value of exfoliative cell cytology for the identification of exudative pleural effusions. This is a retrospective study of the patients with an exudative pleural effusion admitted at our clinic in the last twenty years. We have conducted the clinical, the cytological findings, and the diagnostic results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The database search yielded 3732 studies for screening with 181 potential studies identified for analysis. After full-text analysis, a total of 36 studies met inclusion criteria 2 3 7–40. A summary of the literature search is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The database search yielded 3732 studies for screening with 181 potential studies identified for analysis. After full-text analysis, a total of 36 studies met inclusion criteria 2 3 7–40. A summary of the literature search is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is more sensitive to detect tumor markers in pleural effusion (2). Exfoliative cytology characterized by high specificity and low sensitivity is often used clinically to distinguish benign and malignant pleural effusion (3). Carcinoembryonic antigen (CEA) is present in endoderm-derived digestive system cancer and normal digestive tract tissues, and also present in a trace amount in normal human serum, which can be used as a diagnostic marker for breast cancer, lung cancer, and colorectal cancer, but its specificity and sensitivity are not high (4).…”
Section: Introductionmentioning
confidence: 99%